Exosomal circRNAs as promising liquid biopsy biomarkers for glioma - Wu, Xiaoke; Shi, Mengmeng; Lian, Yajun; Zhang, Haifeng (Frontiers in Immunology, 2023)
Liquid biopsy strategies enable the noninvasive detection of changes in the levels of circulating biomarkers in body fluid samples, providing an opportunity to diagnose, dynamically monitor, and treat a range of diseases, including cancers. Glioma is among the most common forms of intracranial malignancy, and affected patients exhibit poor prognostic outcomes. As such, diagnosing and treating this disease in its early stages is critical to optimal patient outcomes. Exosomal circular RNAs (circRNAs) play roles in both the onset and progression of glioma. The deepening understanding of exosomes and the continuous development of detection technology. Therefore, detecting exosomal circRNAs by liquid biopsy is an important mean to monitor the dynamic changes of glioma. The present review offers an overview of the circulating liquid biopsy biomarkers associated with this cancer type and the potential application of exosomal circRNAs as tools to guide the diagnosis, treatment, and prognostic evaluation of glioma patients in a dynamic manner as this disease progresses.